Novel Method for Determining Standard Enthalpy and Entropy of Volatilisation of Chromia Exposed to Humidified Oxygen at 298 K Based on Transport Theory of Multicomponent Gas Mixtures - Thammaporn Thublaor; Watcharapon Tengprasert; Grid Suparapinyopapkul; Thanasak Nilsonthi; Walairat Chandra-ambhorn; Somrerk Chandra-ambhorn (My University, 2025)
Based on the transport theory of multicomponent gas mixtures, we proposed an expression for determining the standard volatilisation enthalpy and entropy of chromia exposed to humidified oxygen at 298 K. The use of this expression could lead to the quantification of those thermodynamic quantities when the mass flux of Cr loss due to the volatilisation of chromia is determined. We thus experimentally measured the mass fluxes of Cr loss due to volatilisation in humidified atmospheres at 873–1073 K. As a result, the standard enthalpy and entropy of the volatilisation of chromia subjected to humidified oxygen at 298 K were quantified, giving the values of 61.1 ± 1.0 kJ mol−1 and −43.0 ± 1.9 J K−1 mol−1, respectively. The measured and calculated mass fluxes of Cr loss due to volatilisation tended to be related to absolute temperature in the Arrhenius-like form. We proposed the use of the line of the mass flux of Cr loss due to volatilisation in an Arrhenius-like diagram, which was shifted by the different thermodynamic data used to graphically assess the reliability of the thermodynamic data obtained from this work and the literature.
Keywords: Volatilisation; Chromia; Standard molar entropy; Thermal and Kinetic Analysis